Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC) Quantitative Analysis of L-Arginine in Freeze-Dried Red Dragon Fruits (Hylocereus polyhizus) - Saad, Wan Mazlina Md; Isha, Mohd Qamarul Aizat; Zan, Muhamad Faizzudin Mohamad; Sallehoddin, Siti Mastura Hanim (Universitas Gadjah Mada, 2025)
Hylocereus polyrhizus is an exotic fruit with distinct bright colors and tastes that make it popular among many regions of the world. The fruit is cultivated worldwide and firmly established as a source of nutrition, thus, making good value in terms of its potential harvesting by various methods. However, prior reviews have documented weak scientific backing sparsely around extraction efficiency and favorable conditions for optimal yield. This study aimed to quantify the crude L-arginine content for both kinds of dragon fruiting by an RP-HPLC isocratic method, thus establishing a reliable and efficient approach for their detection. This study has revealed that short extraction times are beneficial in retaining L-arginine content since more extended extractions can result in the degradation of other components. Thus, this study opens further avenues toward exploring red dragon fruit as a natural source of L-arginine and advancing functional and nutraceutical products.